The Impact of Work Motivation on Teacher Performance - Ahyani, Nur; Fitria, Happy (Graduate Program Magister Manajemen Pendidikan, 2022)
The purpose of this research is to determine and analyze the effect of teacher work motivation on the performance of SMK teachers in the Banyuasin III Ogan Ilir District of South Sumatra. This is a quantitative study using a survey method. This study was conducted in State Vocational High Schools Banyuasin III and Vocational High Schools, with 80 teachers serving as respondents. Questionnaires and documentation are used to collect data. Construction and content validity are used in the validity test. Cronbach's Alpha is used in the reliability test. The normality, homogeneity, and linearity tests were used in the analysis prerequisite test, and the data were analyzed using descriptive and inferential data analysis techniques. The findings revealed that motivation had an effect on the performance of SMK teachers.